Centralized and Mapped GIS Web-Based Covid-19 Data Reporting Application with The Waterfall Method: (Case Study: Information Communication Department of North Sumatra Province) - Rizki Muliono (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
Covid-19 pandemic cases are currently increasing and expanding throughout the world, especially in Indonesia in the province of North Sumatra. Data on the number of cases spread in the province of North Sumatra which is summarized and published, sometimes there are still disputes over the number and lack of organization in the number of records and their distribution, so there are often errors in the data collected by the health department and which will be published to the public. The case study in this research is the design of an information system that regulates the process of recording, moving, accumulating, and mapping GIS data maps to the publication of Positive case data, Patient Under Surveillance, Polymerase Chain Reaction, and Rapid Test results directly through a web-based covid-19 data reporting application. Sourced from each user of every health facility in each district and city from each sub-district in the province of North Sumatra to support the accuracy of data in decision-making built at the North Sumatra Province Information and Communication Office. The method used in developing the application uses the waterfall method, starting from the needs analysis stage, design, implementation to testing until maintenance. The results of the implementation and testing were carried out using the Blackbox and Whitebox methods. Presentation of GIS web data using google maps has not used a threshold value based on a calculated algorithm, but still uses the determination of crisp values so that the results cannot be said to be relevant as a determinant.